The Factors Affecting Turnover Intention, with the Moderating Role of Intrinsic Intention in Jordanian Five-Star Hotels - Ayman Mousa Ali, Jarwan; Rashidah Mohamad, Ibrahim (International Journal of Engineering and Technology, 2019)
In majority of industries, the issue of high rates of turnover has always exists as a result of which several studies have been dedicated to it, particularly in the hospitality industry context. This study examined the moderating effect of intrinsic motivation on the relationship between factors affecting turnover intention namely, HRMs and work engagement in Jordanian five-star hotels. The study provided details of the findings in every theme highlighted and described the relationships between the factors, using one single model. This study also conducted a comprehensive review of literature and presented quantitative findings on turnover intention from Jordan. Based on the findings, there is a positive and significant relationship between HRMs and work engagement, and turnover intention, with the moderating role of intrinsic motivation. The study has implications to theory in that it provided an expansive explanation of the outcomes of HRMs and work engagement in five-star hotels and their connection to the employees’ turnover intentions.